Contribution à l'étude de l'ontogenèse du système immunitaire chez l'huître creuse Crassostrea gigas - Tirape Bajana, Ana (Université Montpellier II, 2007)
The interest for the understanding of the immune mechanisms in the oyster, Crassotrea gigas has been considerably increased these last years, mainly because of economie losses due to diseases which affected the continuity of this species. The studies of these mechanisms contributes to a better understanding of the differential susceptibilities observed in this species against various pathogens. In the present study, our goal was to define the ontogenesis of immune system in C. gigas during the development, by functional genomic approaches. The studies have been focalized on the analyses of expression and localization of effectors previously identified in adult oysters as implicated in immunity. We have shown, in particular, that hemocytes appear in the grastrula-trochophore stages. The acquisition of immunocompetence in the first larval stages has been shown using bacterial challenges, underlining the implication of hemocytes and various effectors. In addition, by SSH approach, we have identified genes differentially expressed in development stages. A putative function has been assigned to 26% of 668 single sequences, leading to a classification in functional categories. Independently of this classification, we have selected 13 ESTs potentially implicated in the biological mechanisms related to stress and immune response, according to their function in the adult oysters or in other species. Finally, we have characterized an original gene, CgMyD88, a component of the signaling pathway NF-KB. This pathway is conserved in evolution and is implicated in particular in the immune related and the development gene regulation in other species. All these results have permitted to show that the immune system, in the oyster early stages, is rudimentary and immature, and appears progressively but quickly after the fertilization. The various patterns of gene expression suggest differences of reactivity to stresses by C. gigas development stages, and thus could explain the susceptibility differences to infections. These ...